Universal role of oxygen in full-visible-region photoluminescence of diamond nanocrystals. (November 2016) - Zhang, Wenxia; Niu, Xianghong; Chen, Xifang; Guo, Xiaoxiao; Wang, Jinlan; Fan, Jiyang
Abstract: Carbon nanocrystals (NCs) exhibit very intricate luminescence and the underlying mechanism remains a mystery and highly debated. Herein we study the luminescence properties of the wet chemistry-derived diamond NCs and observe peculiar phenomenon of concurrent multiband luminescence across the whole visible region in them. The surface structural and luminescence investigation in conjunction with density functional theory calculation reveal fruitful oxygen-related surface defects in these diamond NCs, and such defects create respective energy levels in the band gap leading to observed luminescences. The calculation shows that these surface traps have either localized or delocalized molecular orbitals, and significant spatial overlap between the highest occupied and lowest unoccupied molecular orbitals of amide-terminated diamond NCs leads to extremely large radiative decay rate as well as unprecedented high quantum yield of 50.4%, in strong contrast with usually low quantum yield of 2.5–5.0% in oxygen-terminated diamond NCs. The result indicates these surface defects are popular and they play important roles in luminescence of the large family of various (graphite, diamond, and C8 ) carbon as well as SiC and C3 N4 NCs.